Corporate Social Responsibility (CSR) Disclosure, Internationalization and Tax Avoidance: Evidence from Indonesia - Asfaro Saragih, Hidayah; Adhariani, Desi; D. Djakman, Chaerul (Jordan Journal of Business Administration, 2023)
This research aims to explore the association between corporate social responsibility (CSR) disclosure, internationalization and tax avoidance of manufacturing companies in Indonesia during (2013-2015). The three-year-period was chosen to represent the last three years before the Global Reporting Initiative (GRI) guidelines, which are used to measure the CSR disclosure, transitioned to GRI Standards, which are more structured, flexible and dynamic. Under the GRI guidelines regime, we expected to document the associations among the three main variables before significant impacts of several events on reporting, such as the transition to new standards, the launch of Sustainable Development Goals (SDGs) and the implementation of tax amnesty in Indonesia in 2016. Empirical analyses were conducted on a sample comprising 153 firm-year observations. Relationships between CSR disclosure and tax avoidance, internationalization and tax avoidance and the moderating role of internationalization were examined using multiple regression analyses, whereas t-test analysis was used to find any significant differences in each association. The results indicated that CSR disclosure positively affects tax avoidance. Meanwhile, internationalization has no effect on tax avoidance and has no moderating role in the positive relationship between CSR disclosure and tax avoidance. This study is among the early research studies which provide evidence from Indonesia, as one of the G20 countries, investigating the associations among CSR disclosure, internationalization and tax avoidance, as well as the moderating role of internationalization, which has not been given much attention in the literature.